Synthesis, evlatuation of functional methacrylates and a computational approach to the reactions of molecules with biological potential - Agopcan, Sesil. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
In this dissertation, experimental and computational methods are used to in vestigate the molecules which are biologically active and have potential in pharma ceutical ﬁeld. This study sheds light on the synthesis procedures of methacrylate based monomers, characterization of the synthesized materials, and also detection of reaction mechanisms, calculations of thermodynamic properties in several reactions. In the ﬁrst three chapters, several methacrylate monomers were investigated which have various biomedical applications. The synthesis and photoinitiating abilities of six novel methacrylate-based monomeric photoinitiators (MPIs) has been carried out. In order to make useful predictions on the reactivities of methacrylates, a relationship between reactivities of 21 methacrylates in free radical polymerization and their chem ical structures were built by a non-linear expression. Finally, methacrylates were used to prepare PEG-based carboxylic-acid functionalized monomers which were incorpo rated into hydrogel scaﬀolds for biomedical applications. In the last three chapters, the reactions of biologically active molecules were analyzed by computational tools. The exo-stereoselectivity of norbornene in the synthesis of thiazolidine derivatives which have diverse biological potential, are clariﬁed by means of Density Functional Theory (DFT). Another biologically active molecule, diclofenac that is used as a drug, was examined to enlighten the degradation mechanism and byproduct formations. Finally, the reactions of cyclohexanone with 3-methyl indole and N-methyl indole, which are the basis of many biologically active compounds, are modeled to determine the origins of regioselectivities.
Keywords: Methacrylic acid.; Methyl methacrylate.; Molecules.